Clinical value of sublingual microcirculatory dysfunction for screening for primary aldosteronism in hypertensive patients - Wang, Wuhao; Liu, Wei; Tang, Yi; Sun, Fang; He, Hongbo; Yan, Zhencheng; Li, Qiang; Zhu, Zhiming (Frontiers in Endocrinology, 2025)
BackgroundMicrocirculation dysfunction commonly occurs in patients with hypertension and diabetes. We aimed to evaluate the changes in sublingual microcirculation among patients with primary aldosteronism (PA), subclinical primary aldosteronism (sPA), essential hypertension (EH), and healthy individuals and aimed to use sublingual microcirculation to screen for PA.MethodsFrom January 2023 to January 2024, we consecutively enrolled 191 hypertensive patients (89 EH patients, 51 sPA patients, and 51 PA patients) and 44 healthy individuals. Sublingual microcirculatory images were captured via side-stream dark-field (SDF) microcirculation microscopy, and total and perfused vessel density (TVD and PVD) were calculated. Patient demographic and laboratory data as well as factors influencing microcirculation parameters were assessed.ResultsCompared with healthy individuals (TVD: 13.97 ± 0.62 mm/mm2; PVD: 11.46 ± 0.53 mm/mm2), EH (12.24 ± 0.56; 9.92 ± 0.34), sPA (11.49 ± 0.51; 9.46 ± 0.33) and PA (10.91 ± 0.68; 8.85 ± 0.43) patients exhibited significant microcirculation dysfunction (TVD and PVD). Receiver operating characteristic (ROC) curve analysis revealed that both TVD and the PVD could effectively mirror microcirculation abnormalities in PA patients. We derived a combined evaluation index (CEI) that was composed of the TVD and the PVD for screening PA. By plotting the receiver operating characteristic (ROC) curve, the CEI (AUC: 0.9818 [0.9660, 0.9977]) demonstrated a superior screening effect for PA compared with the aldosterone-to-renin ratio (ARR, AUC: 0.9505 [0.9194, 0.9817]).ConclusionsPatients with PA had marked microcirculatory dysfunction, which was strongly associated with the ARR. Sublingual microcirculation might be a noninvasive method for the early detection of primary aldosteronism in hypertensive patients.